2016
DOI: 10.1093/jxb/erw005
|View full text |Cite
|
Sign up to set email alerts
|

Plant basal resistance to nematodes: an update

Abstract: Most plant-parasitic nematodes are obligate biotrophs feeding on the roots of their hosts. Whereas ectoparasites remain on the root surface and feed on the outer cell layers, endoparasitic nematodes enter the host to parasitize cells around or within the central cylinder. Nematode invasion and feeding causes tissue damage which may, in turn, lead to the activation of host basal defence responses. Hitherto, research interests in plant-nematode interaction have emphasized effector-triggered immunity rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 105 publications
1
113
0
2
Order By: Relevance
“…However, DAMPs have not yet been identified in plant–nematode interactions. Although the activation of basal defence responses remains underexplored, numerous reviews have shed light on their relevance to identify key molecular players that are involved at early stages of infection (Feng and Shan, 2014; Holbein et al , 2016). …”
Section: Section I: Plant Basal Defence the Apoplast And The Redox Bmentioning
confidence: 99%
See 2 more Smart Citations
“…However, DAMPs have not yet been identified in plant–nematode interactions. Although the activation of basal defence responses remains underexplored, numerous reviews have shed light on their relevance to identify key molecular players that are involved at early stages of infection (Feng and Shan, 2014; Holbein et al , 2016). …”
Section: Section I: Plant Basal Defence the Apoplast And The Redox Bmentioning
confidence: 99%
“…It seems that PAO enzymatic activity plays a pivotal role in cellular redox homeostasis in response to pathogen infection. Following these findings, it was proposed that PPNs might modulate the production of reactive species, not as toxic compounds, but as signalling molecules to activate antioxidant pathways (Goverse and Smant, 2014; Holbein et al , 2016). …”
Section: Section I: Plant Basal Defence the Apoplast And The Redox Bmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no PRR that recognises a nematode-associated molecular pattern (NAMP) has been identified [18]. However, some recent work suggests that nematode infection triggers PTI responses in host through surface-localised receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Suseela et al (in review) observed positive, and sometimes sub-additive, effects of eCO 2 and warming on the amount of suberin and individual suberin monomers in plant roots. If these plant biomolecules inhibit plantfeeding nematodes (Biederman and Boutton, 2009;Holbein et al, 2016), this result could help explain the negative, sub-additive effects of eCO 2 and warming on the abundance of plant-feeding nematodes (Fig. 1).…”
Section: Bacteriafeedingmentioning
confidence: 99%